3D temperature mapping of a ceramic shell mould in investment casting process via infrared thermography. Issue 1 (2nd January 2020) - Greco, Carlo Salvatore; Paolillo, Gerardo; Contino, Mattia; Caramiello, Ciro; Di Foggia, Michele; Cardone, Gennaro
ABSTRACT: Investment casting is a leading technique to manufacture very reliable components. The design and the optimization of this process are usually performed by simulation software and/or by means of simplified models based on heat transfer coefficients obtained by solving the inverse heat conduction problem (IHCP). Both methods require experimental tests, that involve temperature measurements, aiming at validating the investment casting simulations or evaluating the heat transfer coefficients in the IHCP. Typically, all these temperature measurements are performed with thermocouples that are characterized by several limits, such as heat transfer alteration, approximate location of the measurement points, and spatial-limited evaluation of the heat transfer coefficients. In order to overcome these limits, the infrared thermography is proposed as an alternative measurement technique. The infrared thermography allows to obtain complete and spatial-accurate information about the surface temperature of an investigated body which, in particular, is a ceramic shell mould in the present work. Since the infrared thermography is a 2D technique, the purpose of this work is to provide a procedure to experimentally reconstruct the 3D temperature surface distribution of this ceramic shell mould in a real industrial environment with all its space and time constraints.